The impact of nanoclay on the performance of polypropylene/OCC fibers/nanoclay composite - Sina Modirahmati (Regional Information Center for Science and Technology (RICeST), 2012)
The impact of  nanoclay  addition on the properties of  polypropylene/ OCC fibers/ nanoclay Composite was investigated. Composites were prepared using 67% polypropylene, 30% OCC fiber, 3% MAPP and three dosages (2.5, 5, 7.5% based on total weight of PP/OCC/MAPP) of  nanoclay. Premix- melting of nanoclay and polypropylene was used to add nanoclay to the composite mixture. Pre-mixed nanoclay/ polypropylene  was melt-mixed with OCC fibers and MAPP and then test samples were made using this compound. The results revealed that addition of nanoclay to polypropylene/OCC fiber composite reduced flexural strength , tensile strength and notched Izod impact strength, but the flexural modulus and tensile modulus of final composite were improved significantly. The influence of nanoclay addition on flexural strength and tensile modulus of composite  was statistically significant at 99% level whereas its effect on tensile strength was statistically significant at 95%. However, the effect of nanoclay on both flexural modulus of elasticity and impact strength was not statistically significant. The addition of nanoclay to the composite reduces the bonding between polypropylene and OCC fibers. In the case of notched Izod strength, nanoclay particles generated stress concentration point within the composite structure initiating easier failure. Water absorption after 2 and 24 hours immersion was reduced.